Answer: x = - 16
y = - 11
Step-by-step explanation:
The given system of linear equations is expressed as
2x - 3y = 1- - - - - - - - - - - - -1
x - 2y = 6 - - - - - - - - - - - -2
We would eliminate x by multiplying equation 1 by 1 and equation 2 by 2. It becomes
2x - 3y = 1- - - - - - - - - - -3
2x - 4y = 12- - - - - - - - - - - -4
Subtracting equation 4 from equation 3, it becomes
y = - 11
Substituting y = - 11 into equation 2, it becomes
x - 2 × - 11 = 6
x + 22 = 6
Subtracting 22 from the left hand side and the right hand side of the equation, it becomes
x + 22 - 22 = 6 - 22
x = - 16